LINGUISTIC CHARACTERISTICS OF RELIGIOUS TEXTS, ITS SIMILARITIES AND DIFFERENCES WITH OTHER FUNCTIONAL STYLE TEXTS (Scientific journal of the Fergana State University, 2023)
This article deals with the linguistic study of religious texts, the issue of religious style in the Uzbek language, its place in the system of functional styles of the Uzbek language, and its similarities and differences with other styles. The similarities and differences between the existing speech styles and the religious style in the Uzbek language are revealed through concrete examples. Also, the linguistic possibilities of religious texts are analyzed based on the grammatical rules of the Uzbek language. The article also lists lexical features that are not characteristic of religious texts.